Pengembangan Instrumen Tes Berpikir Kritis Berbasis Pendekatan Socio Scientific Issues (SSI) pada Materi Virus: (Development of a Critical Thinking Test Instrument Based on the Socio-Scientific Issues (SSI) Approach on Virus Material) - Rahmatiya, Rahmatiya; Dama, Lilan; Usman, Nurul Fajryani; Retnowati, Yuliana; Mustaqimah, Nur (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2026)
This study aims to analyze the development of a critical thinking test instrument based on the Socio-Scientific Issue (SSI) approach. The abstract nature of virus material demands learning and evaluation that not only emphasizes memorization of concepts, but also connects the concept of viruses with real-life problems. Therefore, an innovative approach is needed to improve students' critical thinking skills with the Socio-Scientific Issue (SSI) approach. The test instruments used by teachers have not accommodated critical thinking skills or teachers still predominantly measure low cognitive abilities, namely C1 and C2. This study uses the Research and Development (R&D) research method along with the ADDIE development model. The population used was 88 grade XI students at MAN 2 Gorontalo Regency. The sample consisted of 35 students who participated in a limited-scale trial with a purposive sampling technique. The results of the research and development that have been carried out, the critical thinking test instrument based on the Socio-Scientific Issue (SSI) approach on virus material was declared